Intergenerational Dynamics of Consumer Complaint Behavior: The Impact of Self-Concept, Values, and Emotional Intelligence - Simanjuntak, Megawati (Universitas Airlangga, 2025)
Background: Complaint behavior allows consumers to express dissatisfaction; however, many remain silent instead of voicing their complaints. Different generational groups may exhibit varying tendencies and influencing factors related to complaint behavior. Objective: The purpose of this research was to compare and examine how self-concept, value, and emotional Intelligence affected the complaint behavior of the baby boomer, Generation X, and Generation Y generations. Method: This cross-sectional study used direct interviews and structured questionnaires. A quota sample technique was used to choose 90 homemakers, 30 from each generation. Results: This study showed significant differences in self-concept between Generation X and baby boomers and Generation Y, as well as in value conflict between Generation X and Y. However, emotional Intelligence did not differ significantly. Self-concept influenced complaint behavior in Generation X, but not in baby boomers and Generation Y. This finding emphasizes the importance of grievance resolution strategies tailored to the characteristics of each generation. Conclusion: Generation X's maturity and productivity contribute to their stronger self-concept and multitasking ability, while Generation Y shows the highest complaint behavior. Efforts to enhance complaint behavior may benefit from focusing on self-concept development, particularly in less expressive generations. Further research could explore other variables influencing complaint behavior. Keywords: consumer complaint behavior; emotional intelligence; self-concept; value